Western Maps/Yanyuwa Meaning: an Interview with John Bradley - Devlin-Glass, Frances; Bradley, John (The Australian Journal of Indigenous Education, 2006)
Abstract In July 2003 an important one-volume text, Forget about Flinders: A Yanyuwa atlas of the south west gulf of Carpentaria(Yanyuwa Families, Bradley & Cameron, 2003) produced in a limited edition of 14 copies, returned to Yanyuwa country and to the families who collaborated with John Bradley and artist Nona Cameron on the project. Subsequently, a second edition of 20 copies has been released, mainly to institutions. It is the most comprehensive attempt yet to restore Yanyuwa names to country and to produce a multilayered, dynamic, history-rich, and bilingual representation of how country is known in this community, and how the central song cycle texts intersect with Yanyuwa tradition. What follows is a condensed and edited interview with Frances Devlin-Glass, in which John Bradley discusses the motivations, the hybridised methodologies employed, the innovations of this new genre, and the pedagogical ends served by this latest iteration of Yanyuwa song cycles.